FEATURES OF THE SENSITIZATION SPECTRUM OF ATOPIC ASTHMA AND RHINITIS - Ikramova Shakhnoza Abdurasulovna (Scholar Express Journals, 2023)
The pathogenetic characteristic of atopic bronchial asthma (BA) is chronic allergic inflammation of the airways, initiated by contact with causally significant allergens. Identification of sensitization is a necessary condition for successful therapy of asthma, and the structure of sensitization may have regional characteristics
Keywords: children; bronchial asthma; treatment; aeroallergens